Structures de taille, croissance et analyse modale de deux espèces de concombres de mer [Holothuria (Roweothuria) poli & Holothuria (Platyperona) sanctori] de la côte de Mostaganem - Belalem, Chahira (My University, 2019)
The present study has focused on the biometric relationships and modal analysis of two species of sea cucumber [Holothuria (Roweothuria) poli & Holothuria (Platyperona) sanctori]. The sampling focused on two stations located at the coast of Mostaganem. The measurements were performed on the individuals of each type of species [The contracted length of the body (LC), wall thickness of the dermis (EP), body wet weight (PHC) and body dry weight (PSC)]. The results showed that individuals of two species are characterized by a significantly negative allometry (whether for weight or linear growth). This Allometry was explained by the fact that sea cucumbers are characterized by an elongated cylindrical shape. Regarding the PHC / PSC ratio, the values obtained for Holothuria (R.) poli differ from those obtained in previous studies, notably the standard value established by (Newell and Courtney, 1965). On the other hand, we recorded a value close to the standard (10/1) at Holothuria (P.) sanctori. This could be due to the consistency of the dermis of this species, which is close to that of Holothuria (P.) fosrkali [Both belong to the same group (presence of Cuvierian tubules and the elasticity of their integuments)]. On the other hand, the results of multivariate analysis of variance showed the existence of a highly significant difference between the two stations. Similarly, we found that the two variables (wall thickness of the dermis "EP" and the body dry weight "PSC") are the most discriminating. Finally, Regarding the modal analysis and the sizes structures, the application of both Bhattacharya (1967) and NORMSEP methods allowed us to describe three cohorts in Holothuria (R.) poli and Holothuria (P.) sanctori.
Keywords: Negative allometry; Modal analysis; Size structures; Cohort; Mostaganem coast.